The Role of Transmembrane Domain Helix-Helix Interactions in the Function of Pentameric Ligand-Gated Ion Channels - Therien, James Patrick Daniel (Université d'Ottawa / University of Ottawa, 2017)
The pentameric ligand gated ion channel super family plays a central role in fast synaptic communication between neurons and at the neuromuscular junction. Extensive studies on the prototypic pLGIC, the Torpedo nicotinic acetylcholine receptor (nAChR) have revealed an exquisite lipid sensitivity, with the nAChR adopting a novel uncoupled conformation in membranes lacking activating anionic and neutral lipids. The lipid-exposed transmembrane alpha-helix, M4, in each homologous subunit likely acts as a lipid sensor. One model proposes that activating lipids promote M4 “binding” to the adjacent alpha-helices, M1 and M3, to enhance interactions between the M4 C-terminus and the Cys-loop of the agonist-binding domain, with such interactions promoting coupling between the agonist site and channel gate. The first part of my thesis indirectly tests this hypothesis by exploring the effects of membrane hydrophobic thickness on nAChR function. Specifically, I tested the hypothesis that thicker membranes, which should promote alignment of M4 parallel to M1/M3 and thus helix-helix interactions, favor a coupled conformation. Although I found that the nAChR is uncoupled in all membranes tested, regardless of hydrophobic thickness, thicker membranes promote transitions from uncoupled to ultimately the desensitized state over the minutes to hours time frame. In contrast to anionic lipids, which influence function primarily via a conformational selection mechanism, membrane hydrophobic thickness influences function via a kinetic mechanism - thick membranes lower the activation energy between uncoupled and coupled conformations to promote conformational transitions. In the second part of my thesis, I used the two prokaryotic homologs, GLIC and ELIC, to explore how amino acid interactions at the interface between M4 and M1/M3 influence channel activity. Alanine scanning mutagenesis of this interface shows that disruption of almost any interaction in GLIC leads to a loss of folding and/or function, while analogous mutations in ELIC typically lead to no change or produce gains in function. Sequence comparisons with other members of the pLGIC superfamily suggest that the transmembrane domains of GLIC and ELIC represent two distinct archetypes. Each archetype may strike a different balance between the need for strong M4 binding to M1/M3 to promote folding and pentamer assembly, and the need for weaker interactions that allow for greater conformational flexibility during function.
Keywords: pLGIC; nAChR; GLIC; ELIC; Protein Structure and Function; Ion Channel